Non-carcass components of heifers supplemented with different energy sources in grazing Tifton 85 (Research, Society and Development, 2020)
The objective of this study was to evaluate the non - carcass components of heifers finished in Tifton 85 pasture supplemented with three different energy sources. Thirty heifers, Charolês x Nelore, were used, with initial mean weight of 26 months and 274.5 kg. The design was completely randomized, with energy sources used: corn, white oat or barley grain, with 10 replicates per treatment. The slaughter weight (SW), empty body weight (EBW) and relationship EBW / SW weights were similar between supplementation strategies. The total organ weight of 100 kg EBW was higher for animals supplemented with corn, 3.43% EBW. The weight of rumen-reticulum relative to 100 kg of EBW was higher for females that received barley, 1.72% EBW, but the weight of the gastrointestinal tract did not differ between the energy sources used. The weight of the peripheral components and the total fat did not differ among the grains used in the supplementation. Supplementation with white oat grain reduces the yield of internal organs and the yield of parts of the gastrointestinal tract, relative to corn grain and barley, respectively..